2018
DOI: 10.1128/jvi.02034-17
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Novel DNA Damage Response Protein, Tankyrase 1 Binding Protein 1, following Adenovirus Infection

Abstract: Infection by most DNA viruses activates a cellular DNA damage response (DDR), which may be to the detriment or advantage of the virus. In the case of adenoviruses, they neutralize antiviral effects of DDR activation by targeting a number of proteins for rapid proteasome-mediated degradation. We have now identified a novel DDR protein, tankyrase 1 binding protein 1 (TNKS1BP1) (also known as Tab182), which is degraded during infection by adenovirus serotype 5 and adenovirus serotype 12. In both cases, degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…E1B has been proposed to act as the substrate recognition component of this complex . The growing list of known targets includes components of the MRN complex, meiotic recombination 11 (Mre11) and Rad 50 , the Bloom helicase , DNA ligase IV , ATRX , p53 , Tat interactive protein‐60 (Tip60) , SPOC1 , Tab 182 , integrin α3 , and SWI/SNF Related, Matrix Associated, Actin Dependent Regulator Of Chromatin, Subfamily A Like 1 . E1B is also responsible for targeting Daxx for degradation, independent of E4Orf6 in HAdV5‐infected cells .…”
Section: Roles Of E1b 55k During Productive Viral Replicationmentioning
confidence: 99%
“…E1B has been proposed to act as the substrate recognition component of this complex . The growing list of known targets includes components of the MRN complex, meiotic recombination 11 (Mre11) and Rad 50 , the Bloom helicase , DNA ligase IV , ATRX , p53 , Tat interactive protein‐60 (Tip60) , SPOC1 , Tab 182 , integrin α3 , and SWI/SNF Related, Matrix Associated, Actin Dependent Regulator Of Chromatin, Subfamily A Like 1 . E1B is also responsible for targeting Daxx for degradation, independent of E4Orf6 in HAdV5‐infected cells .…”
Section: Roles Of E1b 55k During Productive Viral Replicationmentioning
confidence: 99%
“…A repression domain for interferon target genes has been mapped to the E1B 55K C-terminus [9], while its N-terminus can interact with the tumor supressor p53, tethering a repressor domain that inhibits p53-dependent transcription [10,11]. The interaction with the viral early E4 Orf6 protein and the cellular proteins Cullin 5, Elongins B and C, and Rbx1 is required for assembly of an E3 Ubiquitin ligase complex [12] that promotes polyubiquitylation and degradation of a growing number of cellular substrates that include components of the DNA Damage Response (DDR), such as Mre11, Rad 50 [13,14], the Bloom helicase [15] and DNA ligase IV [16,17], as well as, ATRX [18], p53 [12,19], Tip 60 [20], SPOC 1 [21], Tab182 [22], and α3 integrin [23]. Interestingly, E1B 55K is also responsible for degradation of the PML nuclear bodies component Daxx without the assembly of the E4 Orf6-dependent Cullin5 E3 Ubiquitin ligase complex [24].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Chinn et al reported that SNPs in IDH1 were significantly associated with HIV infection, three of which were found in transcription factors binding sites (Chinn et al, 2010). Similarly, CNOT7 and ADAP2, both down-regulated in severe malaria, were previously reported to have a protective role during viral infections (Shu et al, 2015;Chalabi Hagkarim et al, 2018). Of the up-regulated genes in severe malaria, TRA2A was found to promote human influenza A virus replication by inhibiting the splicing of the NS segment of its mRNA (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%